The Correlations Between Effective Interpersonal Communication and Barriers in The Adjustment of The New Students - Hastuti, Ratna; Dwi Nugroho, Agus; Gumilang Berlian, Alang (Lafadz Jaya Publisher, 2024)
The purpose of this study was to examine the correlations between effective interpersonal communication and barriers in the adjustment of the new student. It was hypothesized that there was a relationship between effective interpersonal communication and barriers in adjustment of the new students; and there was a negative correlation between effective interpersonal communication and barriers in adjustment. The first added hypothesis was that there were differences barriers in adjustment between students group based on lesson selection no used non cognitive test and used non cognitive test. The second added hypothesized that there were differences of barriers in adjustment based on sex. The subjects were 64 students on several faculties in The Gadjah Mada University Yogyakarta; 31 males & 33 females; 34 no used non cognitive tests and 30 used non cognitive tests, academic period 2003/2004 S-1 regular. Two scales were applied to measure barriers in adjustment and effective interpersonal communication. The results of the study showed that there were negative correlations between effective interpersonal communication and barriers in adjustment (F - 1.040, p -; 0.002; p < 0.01). In the student’s group-based test selection, there were no differences barriers in adjustment between students group no used non cognitive test and students group used non cognitive test (F = 1.040, p = 0.322; p < 0.01). In the students group based on sex, there was no difference of barriers in adjustment between male and female (F = 1.040. p = 0.907; p < 0.01).